Modeled Walleye Regulation Outcomes in a Midwestern Reservoir with Varying Forage and Walleye Density. (23rd December 2021) - Krogman, Rebecca M.; Dodd, Benjamin J.; Otting, Andy; Weber, Michael J.; Weber, Robert E.
Abstract: In a put‐grow‐take fishery, management of Walleye Sander vitreus may require length‐based regulation and depends on population dynamics such as growth, which in turn depends on forage. Big Creek Lake, an important Iowa Walleye fishery, underwent forage changes twice within two decades. Concurrently, Walleye density changed due to increased stocking and reduced emigration, resulting in four scenarios: (1) low‐density Walleye with Gizzard Shad Dorosoma cepedianum forage (period A: 1998–2000), (2) low‐density Walleye with centrarchid or percid forage (period B: 2006–2008), (3) high‐density Walleye with centrarchid or percid forage (period C: 2013–2015), and (4) high‐density Walleye with Gizzard Shad forage (period D: 2019). We examined Walleye population dynamics and relative effects of four length‐based regulations during each period. Walleye in Big Creek Lake likely experienced density‐dependent effects when Walleye density was high and Gizzard Shad were absent, resulting in depressed growth, low condition, increased natural mortality, reduced exploitation, and ineffectiveness of regulations. At lower Walleye densities, the centrarchid or percid forage supported Walleye growth and condition equivalent to when Gizzard Shad were present. Fishing regulations for enhancing Walleye size distribution or yield differed over time due to shifting population dynamics and angler exploitation and were notably ineffective during period C. The preferred regulation for the current scenario (high‐density Walleye with Gizzard Shad) depends on angler preferences for higher catch or larger fish. Big Creek Lake's Walleye fishery provided a useful demonstration of how rapidly a population can respond to changes in density and forage and, therefore, how dynamic fishery management needs to be.